Management of Guidance and Counseling Services in Preventing and Addressing Online Gambling Behavior Among Vocational High School Students in Banjarmasin - Muhammad Yuliansyah; Sanusi Sanusi; Nadzmi Akbar; Kasypul Anwar; Murdiansyah Herman (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Online gambling has become a pressing concern among adolescents, particularly in digitally literate environments, contributing to behavioral, financial, and academic challenges in schools. This study examines the management of guidance and counseling (BK) services to prevent and address student involvement in online gambling at SMKN 3 Banjarmasin, a vocational high school in Indonesia. A qualitative descriptive design was employed, involving four informants: the school principal, one BK teacher, and two students, all purposively selected based on direct experience with the phenomenon. Data were collected through semi-structured interviews and classroom and schoolyard observations, and analyzed using Miles and Huberman’s interactive model of data reduction, display, and conclusion drawing. The findings indicate that BK management follows three main stages—planning, implementation, and evaluation. Preventive measures include counseling sessions, classroom guidance, and ongoing student monitoring, while intervention strategies involve parental collaboration, coordination with teachers, and application of school disciplinary policies. This study proposes a procedural management model for integrating guidance and counseling into school frameworks to address online gambling, emphasizing coordination, monitoring, and evaluation. Peer influence and digital exposure remain key challenges. Limitations include the small number of informants and the single-school context, which may affect the transferability of the findings. Future research should involve multiple schools, larger participant samples, and policy-based frameworks for sustainable prevention of online gambling among students.